The role of three glucose/lipid composite indices (CHG, TYG, and AIP) in predicting carotid plaque and fatty liver outcomes: a retrospective cohort study - Li, Dan; Xu, Zhaohui; Wang, Feifei; Hu, Yinqin; Zhang, Xinyu; Yang, Jiahui; Wan, Qiqi; Zhang, Ning; Liu, Yongming (Frontiers in Endocrinology, 2025)
BackgroundCarotid plaque and fatty liver disease, as important target organ damages of metabolic disorders, have undergone a steady increase in prevalence. Cholesterol, high-density lipoprotein, and glucose index (CHG), triglyceride–glucose index (TYG), and atherogenic index of plasma (AIP) are tools for assessing metabolic abnormalities. This research aimed to evaluate the potential of three indicators in predicting carotid plaque and fatty liver.MethodsThis study is based on longitudinal health examination data from workers at Ansteel Group in China in 2019. The follow-up period was five years, with the outcomes being the occurrence of carotid plaque or fatty liver events. Multivariate Cox regression analysis was used to examine the relationship between CHG, TYG, and AIP with the outcomes of carotid artery plaque and fatty liver. We used restricted cubic spline (RCS) curves to analyze the dose-response relationship between the three indices and the outcomes. We employed receiver operating characteristic (ROC) curves to evaluate the predictive ability of these indices. Finally, we also conducted subgroup analyses.ResultsCarotid plaque events developed in 659 workers (18.40%), and fatty liver in 375 workers (10.47%) during the follow-up period. Cox analysis revealed that the three indices were correlated with carotid plaque (Q3 vs Q1, CHG: HR 2.13, P < 0.001; TYG: HR 1.20, P = 0.006; AIP: HR 1.95, P < 0.001) and fatty liver (Q3 vs Q1, CHG: HR 2.46, P < 0.001; TYG: HR 1.75, P < 0.001; AIP: HR 3.47, P < 0.001). RCS indicated that the three indices were linearly related to carotid plaque and nonlinearly (inverted L-shaped) related to fatty liver. ROC curve analysis revealed that CHG had a stronger predictive ability for carotid plaque outcomes, while TYG had a stronger predictive ability for fatty liver. Subgroup analysis results showed that gender and BMI interacted with the three indicators in relation to outcomes.ConclusionsOur research found that CHG, TYG, and AIP were positively correlated with carotid plaque and fatty liver. Moreover, CHG demonstrated superior predictive ability for carotid plaque outcomes, whereas TYG demonstrated better performance for fatty liver outcomes.